2016
DOI: 10.1039/c5ra24835c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of protic ionic liquids as thermoelectrochemical materials

Abstract: PILs have been designed and synthesized for energy harvesting applications. The module exhibited a maximum Se value of 420 μV K−1 which is the highest reported for PILs with the I−/I3− redox couple.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 53 publications
1
15
0
1
Order By: Relevance
“…Black, et al showed that lithium bis(trifluoromethylsulfonyl)imide (Li[NTf2])/tetraglyme(G4) mixing resulted in thermoelectrochemical electrolytes when combined with lithium metal electrodes [107]. Se results of the I -/I 3 [110].…”
Section: Se= ∆E/∆t (4)mentioning
confidence: 99%
“…Black, et al showed that lithium bis(trifluoromethylsulfonyl)imide (Li[NTf2])/tetraglyme(G4) mixing resulted in thermoelectrochemical electrolytes when combined with lithium metal electrodes [107]. Se results of the I -/I 3 [110].…”
Section: Se= ∆E/∆t (4)mentioning
confidence: 99%
“…The first reported functioning TEC with an ionic liquid was produced by Abraham, et al [104]. As [110].…”
Section: Se= ∂E/ ∂T = −∆S/nf (5)mentioning
confidence: 99%
“…Với vai trò là xúc tác cho phản ứng, chất lỏng ion có nhiều tính chất vật lý nổi bật đã được nghiên cứu như áp suất hơi bão hòa thấp, nhiệt độ nóng chảy thấp, quá trình điều chế đơn giản, độ nhớt cao, độ dẫn ion cao, độ phân cực thấp, dễ dàng thu hồi và tái sử dụng [18]. Ngoài ra, chất lỏng ion còn được ứng dụng nhiều trong lĩnh vực khác như chất điện giải trong pin, hấp thụ khí, dung môi ly trích,… [19,20].…”
Section: Mở đầUunclassified